Sistem Inovasi : Peran dan Tantangan dalam Mendukung Pembangunan Pertanian - Witjaksono, Julian (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
Innovation system as the added value for economic growth needs more attention not only on the national scale but also on the regional scale, particularly in agriculture. This study is the assessment of the innovation system particularly about the achievement of the agricultural innovation system in regional development. The research method was employed in 2015 by purposive sampling with the number of respondents was about 30. The respondents came from the stakeholders of farmers, university, private sector, and regional research institution. The sample area has been chosen in Konawe District, North Konawe District and East Kolaka as represent of this research. This paper aims to describe the data and information related to the evaluation worked on regional research and development institutions in supporting the innovation system. This assessment has shown that the development of the agricultural innovation system in regional autonomy faced some constraints and weaknesses, viz. Less synchronization, less coordination, lack of research funding, and less infrastructure.